Stylistic differences and translation adaptation of Chinese and English reports from the perspective of corpus translation studies - Feng, Chuhan (International Scientific Technical and Economic Research, 2025)
With the acceleration of globalization, the translation demand for Chinese and English reports is increasing. There are significant style differences between Chinese and English in terms of grammatical structure, vocabulary usage, discourse organization, etc., which puts higher requirements on the translation process. From the perspective of corpus translation research, this paper explores the language style differences and translation adaptation strategies in the translation of Chinese and English reports. By constructing a bilingual corpus of Chinese and English reports and combining data analysis methods, the differences in grammar, vocabulary and discourse structure are deeply analyzed. The study shows that in the translation of Chinese and English reports, translators need to adopt multiple strategies such as cultural adaptation, linguistic adaptation and functional adaptation according to the cultural background and language characteristics of different languages ​​to ensure that the translated text can meet the style and cultural norms of the target language while faithfully conveying information. In addition, this paper also demonstrates the application of corpus translation research methods in translation practice, emphasizing the importance of big data analysis in revealing style differences and translation strategies. The research results provide theoretical support and practical guidance for improving the quality of Chinese and English report translation and promoting cross-cultural communication.